COMPARISON OF PREDICTORS OF DIFFICULT INTUBATION - SANGEETA, LAMBA; SURENDRA KUMAR, SETHI; VEENA, PATODI; NEENA, JAIN; POOJA, MATHUR; KANGCHAI, CHAUDHURI (International Journal of Clinical and Biomedical Research, 2016)
Context: Unanticipated difficult laryngoscopy and tracheal intubation always remain a primary concern for an anaesthesiologist as the failure to maintain a patent airway during induction of anaesthesia may lead to anaesthesia related morbidity and mortality. Aims: The aim of our study was to predict difficult intubation and to identify best predictor(s) among them and also to compare the sensitivity, specificity, positive predictive value, negative predictive value and accuracy of various airway parameters.Airway parameters taken in our study were Modified Mallampati Classification (MMT), Thyromental Distance (TMD), Sternomental Distance (SMD), Interincisor Gap (IIG), Upper Lip Bite Test (ULBT), Degree of Neck Extension (DNE), Anterior Subluxation of Mandible (ASM) and Protruding Teeth (PT). Methods and Material: 350 patients of ASA Grade 1 and 2 scheduled for various elective surgeries under general anaesthesia were included in our study and were assessed preoperatively for different airway parameters. Intraoperatively all patients were classified as difficult and easy intubation group according to Cormack and Lehane laryngoscopic view. Clinical data of each test was collected, tabulated and analyzed to obtain the sensitivity, specificity, positive predictive value and negative predictive value. Results: The upper lip bite test had the highest sensitivity (80%); Anterior subluxation of mandible had highest specificity (99.06%) and both of above were most accurate tests. The overall incidence of difficult intubation was 8.57%. Conclusion: Upper lip bite test was the best predictor of difficult intubation and it should be included as a routine test along with Modified mallampati test in preanaesthetic evaluation.